2021
DOI: 10.2147/ijgm.s297762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Analytical Performance of Seven Rapid Antigen Detection Kits for Detection of SARS-CoV-2 Virus

Abstract: Background: Early diagnosis of the novel coronavirus disease of 2019 (COVID-19) in asymptomatic and symptomatic patients is crucial to identify infectious individuals and to help prevent the spread of the virus in the community. Several assays have been developed and are in use in today's clinical practice. These assays vary in their analytical and clinical performance. For an accurate diagnosis, medical professionals must become more familiar with the test's utility to select the most appropriate test. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 15 publications
4
39
0
Order By: Relevance
“…We could not detect viral protein in penis tissue by immunohistology, possibly due to comparably low viral RNA load in the penis. This result was not surprising since recent studies show that COVID-19 isolation is unlikely from samples with low RNA loads [ 4 ]. H&E staining from our specimens did not show significant results compared to previous studies in which COVID-19 infection caused mild to moderate accumulation of lymphomonocytic inflammatory cells in a perivascular or subendothelial distribution [ 5 ].…”
Section: Discussionmentioning
confidence: 77%
“…We could not detect viral protein in penis tissue by immunohistology, possibly due to comparably low viral RNA load in the penis. This result was not surprising since recent studies show that COVID-19 isolation is unlikely from samples with low RNA loads [ 4 ]. H&E staining from our specimens did not show significant results compared to previous studies in which COVID-19 infection caused mild to moderate accumulation of lymphomonocytic inflammatory cells in a perivascular or subendothelial distribution [ 5 ].…”
Section: Discussionmentioning
confidence: 77%
“…Ag-RDT has been reported to have high specificity, but its use in clinical diagnosis is sometimes questioned because of its low sensitivity. Recent studies showed Ag-RDT is unable to detect SARS-CoV-2 at a Ct value of more than 19 [ 22 ]. Other reports have revealed the diagnostic sensitivity of Ag-RDT to be 95% at Ct values < 25 but declines drastically to 20–40% when the Ct value is > 25 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible interference of time of testing cannot be ruled out. Some researchers revealed that testing less than 5 days from the onset of symptoms increases sensitivity (9,10,23,31). It is inconsistent with previous reports that a load of infectious virus decreases after 7-10 days (10,45).…”
Section: Discussionmentioning
confidence: 84%
“…Summary ROC curves constructed for all assays based on Monte Carlo simulations are shown in Fig.2. It did not apply to assessing the false results, because 7 studies (35%) did not focus on false results (8,10,23, 28,31,33, 38,39). Some of the current kinds of literature which focused on Ab rapid tests were excluded due to reporting the results as the separate sensitivity for IgG and IgM or analyzed data based on onset of symptoms(4,40).…”
mentioning
confidence: 99%